(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The article presents the theoretical foundations of the collective performance Nós sós, carried out during the physical isolation imposed by the Covid-19 pandemic. Due to the impossibility of the meeting, the collective connected in a symbolic way, through the making of ritual masks and movements and gestures that evoke warrior entities. The tension between the search for the construction of collectivities and the isolation that can intensify individualism is discussed, as well as the need to reflect on the community, not only of humans, but of all living beings that inhabit the Earth. The mask is one of the reasons that allow such a discussion, since it is opposed to the immunizing mask as an individualizing border and the ritual mask capable of activating the connection with the forces of animal or plant bodies.